Intrathorakale Anastomoseninsuffizienz nach Ösophagus- und Kardiaresektion: Definition und Validierung der neuen CAES-Klassifikation = Intrathoracic anastomotic leakage following esophageal and cardial resection : Definition and validation of a new severity grading classification - Schaible, Anja; Schmidt, Thomas; Diener, Markus K.; Hinz, Ulf; Sauer, Peter (Der Chirurg, 2018)
BackgroundAnastomotic leakage is still the most frequent cause of postoperative mortality following esophageal and cardial surgery. The German Advanced Surgical Study Group recommended that endoscopy should be the first diagnostic method if leakage is suspected. The German Surgical Endoscopy Association developed and validated a definition and severity classification of anastomotic leakage following esophageal and cardial resection.Material and methodsIn 2010 the international study group on insufficiency published a definition and severity grading of anastomotic leakage following anterior resection of the rectum, which was validated in 2013. The severity of anastomotic leakage should be graded according to the impact on clinical management: type I requires only conservative management, type II requires interventional radiological or endoscopic treatment and type III requires surgical revision. In contrast to the rectal classification type III is divided into a category without (type IIIa) or with (type IIIb) conduit resection and diversion. The validation was carried out on a 10-year collective from the university hospitals in Heidelberg and Tübingen.ResultsFrom 2006-2015 all 92 patients who developed an anastomotic leakage following esophageal and cardial resection were enrolled in the study. We found a significant increase in the length of stay in the intensive care unit (ICU) with increasing classification type (p < 0.0143). Furthermore, there was a significant correlation with the general classification of postoperative complications according to Clavien-Dindo as well as with mortality (p < 0.001).DiscussionStandardized parameters are the prerequisite to be able to compare the results between hospitals and studies. The validation of the suggested classification shows that the differentiation between the groups is substantiated by the correlation to the length of ICU stay, Clavien-Dindo and mortality and will therefore contribute to a better comparability of data on leakage following esophageal resection in the future.